MINAT BELAJAR PESERTA DIDIK TERHADAP PEMBELAJARAN SISTEM BLOK PADA PELAJARAN PENJAS DI SMTI PONTIANAK - Wibowo, Arief Dwi; Haetami, Mimi; Fitriana, Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research discussed about the block system learning model in vocational productive subjects at SMK-SMTI Pontianak. The school held the productive subjects about 2 (two) up to 3 (three) weeks. Therefore, the students did not get physical education subject and the schedule lesson is random in every week. The aim of this research was to know students’ interest in block system learning in physical education subject at SMK-SMTI Pontianak. The research method was a quantitative descriptive study. The researcher also used the survey method. The sample of this research were the eleventh grade students of SMK-SMTI Pontianak, which consist73 students. The instrument of research was a questionnaire. Technique of data collection was to pour the frequency into a percentage. The results of this research was students’ interest to block system learning in physical education subject at SMK-SMTI Pontianak was very high with the highest frequency considering in the high category with 38 students or 52.05%. Therefore, the researcher concluded that students’ interest in block system learning in physical education subject at SMK-SMTI Pontianak was very high which 38 students or 52.05% and high which 35 students or 47.95%. Keywords: block system, learning interest, physical education.